Dynamic Development of Children: findings from the first three waves of LSAC data - Zhou, A (Sydney, 2013)
This report presents the findings from a study that investigates the dynamic development of children in Australia using data from the Growing up in Australia: the Longitudinal Study of Australian Children (LSAC). The study aims to determine how Australian children develop in the three domains of child functioning: physical/health development, social/emotional functioning and cognitive/academic performance. It examined the roles of family income and maternal education, and the extent to which they predict/explain children’s developmental trajectories in those three domains. The study contributes towards building a local knowledge base about how Australian children are developing. The report is based on the first three waves of data collection for the K cohort of 4,983 young children (i.e. aged 4-5 years). Both descriptive analysis and mixed effects models that are appropriate for the analysis of longitudinal data were employed. This study has produced a number of interesting findings. The developmental trajectories of Australian children in the physical/health, social/emotional and cognitive/academic domains vary with family income, maternal education and child characteristics such as sex and Aboriginality. However, the importance of these factors in predicting children’s developmental trajectories in these domains can’t be over stated. It is found that inclusion of these predictors explains only a small portion of the variation in initial status (2-16%) and even smaller portion of the variation in rate of change (0-7%) across the three outcome domains.
Keywords: Child Development -- Emotional; Child Development -- Cognitive; Child Development -- Social; Families -- Socio-economic status; Families and relationships; Childhood and child development; Families; Child Development; Socio-economic status; Cognitive; Emotional; Social; Families and relationships; Childhood and child development